Kualitas Pelayanan Publik Bagi Pasien Ugd Bpjs Kesehatan Di Puskesmas Kalosi Kecamatan Alla Kabupaten Enrekang - Wahyuni, Sri; Mahsyar, Abdul; Rahim, Samsir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study aimed to find out the quality of BPJS Health Emergency Services at the Kalosi Health Center, Alla District, Enrekang Regency seen from the theory of service quality standards according to Parasurama 2017, namely direct evidence, reliability, responsiveness. assurance and empathy The research method used  descriptive qualitative. Data collecting technique used observation, documentation and direct interviews. The results showed 5 indicators of Public Service Quality for ER Patients BPJS Health D at Kalosi Health Center, namely indicator 1) Direct evidence, that the existing facilities and infrastructure at the Public health center were still lacking and not functioning 2) Reliability, that Reliability and trust in increasing again. 3) The power of administrative and medical staff was still not maximized, it  needed to be responsive, the skills of doctors and nurses in examining patients were good 4) Guarantees, the ability of doctors and nurses in services could  be trusted by patients although there were still some things which had to be improved, such as unfriendly attitudes and young medical officers and new administrative officers. 5) Empathy of the nurse had taken good care of the patient. Keywords: Quality of service, BPJS Kesehatan Emergency Room, Public health center.